Newly uncovered wall paintings by Carlo Innocenzo Carloni in the main staircase of the Clam-Gallas palace in Prague - Zapletalová, Jana 1981-; Krummholz, Martin 1974- (2021)
During the reconstruction of the Clam-Gallas Palace in Prague, the original painted decoration of the main staircase hall walls, which had been hidden for almost two centuries, was uncovered. A style analysis and research in period sources carried out by the authors has made possible a safe attribution of the paintings to Carlo Innocenzo Carloni, who created them on the basis of a contract signed in May 1727. Carlo Innocenzo Carloni realised a series of wall paintings in the state interiors of the whole west palace wing, but today only some of them have survived. The authors of the article also refer to the period inventories of Carloni’s bozzetti (preliminary oil sketches), which refer to some themes in Carloni’s surviving and lost work. These provide some help with the iconographic determination of the newly uncovered paintings in the stairway hall, which is not wholly clear. Comparison of inventories with the artists known realisations makes it clear that Carloni repeated in Prague the themes used in other places. He does not seem to have been the author of the decoration of the interiors of the east wing (including the later library). The newly uncovered paintings on the walls enhance the exceptionally high-quality, comprehensive artistic decoration of the remarkable stairway hall of the Clam-Gallas Palace, which represents one of the most important creations of the European High Baroque.
Keywords: Carlone, Carlo Innocenzo -- 1686-1775; Wandmalerei; Palais Clam-Gallas -- Prag